High Diversity and Functional Potential of Undescribed “Acidobacteriota” in Danish Wastewater Treatment Plants - Kristensen, Jannie Munk; Singleton, Caitlin; Clegg, Lee-Ann; Petriglieri, Francesca; Nielsen, Per Halkjaer (Frontiers in Microbiology, 2021)
Microbial communities in water resource recovery facilities encompass a large diversity of poorly characterized lineages that could have undescribed process-critical functions. Recently, it was shown that taxa belonging to “Acidobacteriota” are abundant in Danish full-scale activated sludge wastewater treatment plants (WWTP), and here we investigated their diversity, distribution, and functional potential. “Acidobacteriota” taxa were identified using a comprehensive full-length 16S rRNA gene reference dataset and amplicon sequencing surveys across 37 WWTPs. Members of this phylum were diverse, belonging to 14 families, eight of which are completely uncharacterized and lack type strains. Several lineages were abundant, with relative abundances of up to 5% of the microbial community. Genome annotation and metabolic reconstruction of 50 high-quality “Acidobacteriota” metagenome-assembled genomes (MAGs) from 19 WWTPs showed high metabolic diversity and potential involvement in nitrogen and phosphorus removal and iron reduction. Fluorescence in situ hybridization (FISH) using newly-designed probes revealed cells with diverse morphologies, predominantly located inside activated sludge flocs. FISH in combination with Raman microspectroscopy revealed ecophysiological traits in probe-defined cells from the families Holophagaceae, Thermoanaerobaculaceae, and Vicinamibacteraceae, and families with the placeholder name of midas_f_502, midas_f_973, and midas_f_1548. Members of these lineages had the potential to be polyphosphate-accumulating organisms (PAOs) as intracellular storage was observed for the key compounds polyphosphate and glycogen.